Accelerated material data generation for viscoplastic material models based on complex LCF and incremental creep tests. (2nd November 2017) - Thiele, Marcus; Gampe, Uwe; Buchmann, Klaus
Abstract: Viscoplastic material models are quite important for realistic characterization of deformation behaviour of high-temperature components. However, their material parameter adjustment is expensive and usually requires extensive material testing. The high-temperature deformation behaviour of cast iron GJS X SiMo 4.1 was determined by accelerated complex material testing methods in order to establish a cost-effective identification of viscoplastic material model parameters. Incremental creep tests with mixed-load and temperature steps, together with relaxation and stepped-tensile tests, were carried out in order to determine the stress-dependent creep strain rate at characteristic temperatures and stresses. The cyclic plastic deformation behaviour was studied with complex low-cycle fatigue (C-LCF) evaluations at varying strain rates, amplitudes and temperatures. Thereafter, the results were employed to identify material model parameters of a Chaboche-type viscoplastic material model, which was applied to represent the cyclic deformation and creep behaviour with a correct representation of strain-rate effects at low strain rates.